Trust of the generation z in artificial intelligence in the assessment of historical events - Mikhail V. Vinichenko; Galina Yu. Nikiporets-Takigawa; Natalia V. Ljapunova; Sergey A. Makushkin; Oхana L. Сhulanova (International Journal of Evaluation and Research in Education (IJERE), 2022)
The article considered the degree of trust of Russian and Slovak students of Generation Z (Gen Z) in artificial intelligence (AI) in the assessment of historical events in the conditions of digital society. The basic empirical methods of the study were a sociological survey and focus group conducted in the context of the COVID 19 pandemic remotely using the resources of the online Google Form and cloud conference platform Zoom. The degree of trust of Russian and Slovak Gen Z students in the general issues of the use of AI, the assessment of historical events by AI generally coincide on fundamental issues and have some contradictions on secondary ones. The analysis of the research data showed that Russian and Slovak Gen Z students have a generally positive attitude to historical information coming from AI. Differences in the degree of trust (not trust) between Russian and Slovak Gen Z students in the presentation of historical information to them by the AI, contradiction in the evaluation of individual historical events were revealed. Gen Z is wary of AI, believing that AI is dangerous for humans and should not be fully trusted in all matters of presentation and assessment of historical events.